Implementation of Religious Moderation Education in Children's Character Development at Tadika Ar Raziq Child Care Centre, Shah Alam, Malaysia - Reylinsa Br Saragih, Nike; Qorib, Muhammad (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The education on religious moderation in children should start from an early age, namely duing the golden period is very important for building the basis of moderate character that is in line with Islamic values. Education plays a role in forming a generation that is intelligent and has good morals. This research aims to understand the importance of strengthening religious moderation in depeloping suboptimal character in early childchood at Tadika Ar Raziq Child Care Centre, Shah Alam, Malaysia. This research uses a qualitative approach, with data collection techniques through observation, interviews and documentation. The research result show that learning religious moderation in early childhood focuses on three aspects: 1) Strengthening the faith, 2) Moral education, and 3) Fostering the value of tolerance. These three aspects are implemented throught effective learning programs, using habitual method and role models. Factor that influence the formation of moderate character in children include environmental factors, as well as support from parents and teacher at school.